The Effect of His-Based Accounting Information System on the Effectiveness of Inpatient Revenue Collection at Bandung Regional General Hospital - Indri Gustirani; Mariana Rachmawati (Dinasti Accounting Review, 2026)
High public expectations regarding the quality of healthcare services require hospitals to optimize human resource performance and effectively integrate operational systems. This study aims to empirically examine the impact of implementing an Accounting Information System on inpatient revenue. Field observations indicate that the management of financial data that is not ye integrated has the potential to lead to operational inefficiencies and revenue leakage. The research method used is quantitative descriptive with an empirical causal analysis approach. The population in this study consists of employees in the accounting, finance, and functional departments at the Bandung City General Hospital. The sample was selected using purposive sampling, comprising 15 respondents. Primary data was collected via a questionnaire and analyzed using simple linear regression, correlation coefficients, the coefficient of determination (R²), and hypothesis testing (t-test). The results of the statistical analysis indicate that the Accounting Information System has a positive and significant effect on inpatient revenue at the Bandung City General Hospital. The Accounting Information System’s ability to present accurate and timely financial data has proven effective in minimizing errors in recording inpatient transactions, thereby directly optimizing revenue for the region or institution. This study recommends a systematic enhancement of operational system capacity to maintain the efficiency of financial services.